2016
DOI: 10.1177/096739111602400914
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Epoxidized Natural Rubber Tread Compound: The Hybrid Reinforcing Effect of Silica and Silane System

Abstract: Modification of natural rubber via epoxidation process increases its compatibility with highly polar filler like silica. In this work, epoxidized natural rubber (ENR) reinforced with silica compound is evaluated for truck tire tread compound. The rheological, physical and dynamic properties as well as the bound rubber content of ENR-silica tread compound are discussed. The results show that ENR-silica compound has high chemically bound rubber indicating the good interaction and bonding between rubber and silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 7 publications
1
21
0
1
Order By: Relevance
“…In these attempts, blends of NR with at least one or more synthetic elastomers selected from the category of cis 1,4-polybutadiene (BR), NR/cis 1,4-polyisoprene rubber (IR), styrene-butadiene-based rubber (SBR), or their derivatives have been reinforced with mono or hybrid fillers such as CB and/or silanized silica as already demonstrated in previous studies [5,7,9]. The emergence of epoxidized natural rubber (ENR), which is reported to exhibit a higher polarity than NR, owing to the epoxide groups in its structure, has opened a new research area that seeks to examine its compatibility with silica for advanced applications including green tire fabrication [12,13]. Sengloyluan et al [14] have recently observed that increasing the mol% content of epoxide groups of ENR increases the tensile properties of ENR-silica-filled compounds than their counterpart NR silica-based compounds, although the curing times were prolonged.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In these attempts, blends of NR with at least one or more synthetic elastomers selected from the category of cis 1,4-polybutadiene (BR), NR/cis 1,4-polyisoprene rubber (IR), styrene-butadiene-based rubber (SBR), or their derivatives have been reinforced with mono or hybrid fillers such as CB and/or silanized silica as already demonstrated in previous studies [5,7,9]. The emergence of epoxidized natural rubber (ENR), which is reported to exhibit a higher polarity than NR, owing to the epoxide groups in its structure, has opened a new research area that seeks to examine its compatibility with silica for advanced applications including green tire fabrication [12,13]. Sengloyluan et al [14] have recently observed that increasing the mol% content of epoxide groups of ENR increases the tensile properties of ENR-silica-filled compounds than their counterpart NR silica-based compounds, although the curing times were prolonged.…”
Section: Introductionmentioning
confidence: 94%
“…They observed that ENR-silica tread compounds showed lower RR, hence reduced fuel consumption, with enhanced wet and ice traction compared with benchmark premium passenger or truck treads. Furthermore, Sarkawi et al [12] had examined ENR-silica for the application of tire tread compound, in which ENR-silica was found to exhibit lower RR and better wet traction compared to NR-carbon black vulcanizates. However, there is currently little research work on ENR used as a component for green tire manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of ENR and silica comes from the hydrogen bonding between the silanol groups of silica with the epoxide group in ENR. The stronger interactions between ENR and silica derived from the silica bonding with the ring opening of ENR; as well as from silica coupling with ENR through silane coupling bonding[33].…”
mentioning
confidence: 99%
“…KPB pada penelitian ini dimodifikasi dari karet alam, karet sintesis SBR dengan bahan pengisi dari biomassa, dan bahan pelunak dari minyak nabati. Modifikasi karet alam dilakukan dengan merubah sifat karet dengan berbagai bahan kimia, bahan pengisi seperti silika yang menghasilkan karet yang kompetibel (Sarkawi et al, 2016). Bahan pengisi penguat yang ditambahkan pada KPB berupa silika, bahan pengisi penambah volume abu terbang batubara (fly ash), dan bahan proses lainnya.…”
Section: Pendahuluanunclassified